Water Quality, Brawn, and Education : The Rural Drinking Water Program in China - Xu, Lixin Colin; Zhang, Jing (World Bank Group, Washington, DC, 2014)
Although previous research has demonstrated the health benefits of water treatment programs, relatively little is known about the effect of water treatment on education. This paper examines the educational benefits to rural youth in China of a major drinking water treatment program started in the 1980s, perhaps the largest of such programs in the world. By employing a cross-sectional data set (constructed from a longitudinal data set covering two decades) with more than 4,700 individuals between 18 and 25 years old, the analysis finds that this health program has improved the individuals' education substantially, increasing the grades of education completed by 1.08 years. The qualitative results hold when the analysis controls for local educational policies and resources, village dummies, and distance of villages to schools, and by instrumenting the water treatment dummy with villages' topographic features, among others. Moreover, three findings render support to the brawn theory of gender division of labor: girls benefit much more from water treatment than boys in schooling attainment; youth with an older brother benefit more than youth with an older sister; and boys gain more body mass than girls do from having access to treated water. The program can account for the gender gap in educational attainment in rural China in the sample period. Young people that had access to treated plant water in early childhood (0-2 years of age) experienced significantly higher gains in education than those who were exposed to treated water after early childhood. The estimates suggest that this program is highly cost-effective.